PENGGUNAAN ANDROID STUDIO DALAM PENGEMBANGAN APLIKASI PEMESANAN TIKET BIOSKOP - Tiara Eka Anggraini; Efmi Maiyana (Journal of Innovation And Future Technology, 2025)
The development of Android-based cinema ticket booking applications is increasingly relevant in addressing the challenges of modernization and the demand for time efficiency. This study aims to design and develop a user-friendly application with modern features such as real-time seat selection and digital payment integration. The research employs the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. Using Android Studio and java, the application incorporates functionalities like seat visualization, payment options, and movie recommendations. The results demonstrate that the application effectively addresses user needs, offering a seamless and efficient booking process. Although the study did not involve direct user surveys, it utilized literature reviews and past studies as references. The implementation of modern technology, such as QR codes for e-tickets, ensures convenience, security, and reduced paper usage. This study provides a solid foundation for future research in developing innovative applications for the entertainment industry.